PENGARUH KELOMPOK REFERENSI TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK WARDAH DIKOTA JAMBI - Maini, Maini (Jurnal Dinamika Manajemen, 2015)
This study aims to simultaneously explain the influence of reference groups (friendship groups, shopping groups, work groups, virtual society groups, and consumer activist groups) on the decision to purchase Wardah cosmetics in the city of Jambi and to explain the variables from the reference groups that are most dominant in influencing the decision to purchase Wardah cosmetics in the city of Jambi. The method used is multiple linear regression. The results of the study concluded that simultaneously and partially reference groups (friendship groups, shopping groups, work groups, virtual community groups, and consumer activist groups) have a significant effect on the decision to purchase Wardah cosmetics in the city of Jambi. This can be proven from the significance probability value which is less than <0.05. This means that simultaneously the five independent variables consisting of friendship groups, shopping groups, work groups, virtual community groups, and consumer activist groups, influence the decision to purchase Wardah cosmetics in the city of Jambi. Partially the independent variables consisting of friendship groups, shopping groups, work groups, virtual community groups, and consumer activist groups also influence the decision to purchase Wardah cosmetics in Jambi City.